Power Centres and Marginal Landscapes: Tracking Pre- and Post-Conquest (Late Iron Age and Medieval) Land-Use in the Cēsis Castle Hinterland, Central Latvia. (4th July 2021) - Brown, Alex; Pluskowski, Aleks
ABSTRACT: During the late Iron Age, the eastern Baltic was inhabited by Finno-Ugric and Baltic speaking societies whose territories were conquered in the thirteenth century as a result of the crusades. This paper examines the degree to which indigenous landscapes were transformed as a result of the crusades, and the evidence for maintenance of indigenous land-use practices. Vegetation and land-use history are reconstructed using palynological data from Cēsis castle and its terriitory. Comparison is made with selected palynological, archaeological and documentary data across Livonia (Latvia and Estonia) and contrasted with the greater impact of the crusades in nearby Prussia. Despite the emergence of key power centres in the medieval period, including towns and castles such as Cēsis, many parts of the rural landscape remained largely unchanged by the crusades, particularly in those more marginal landscapes studied in this paper. Lower intensity land-use can be linked to poor agricultural soils but also reflect the limited colonisation of rural landscapes beyond the major towns and castles. Indigenous societies and practices survived to a greater degree, with later agricultural intensification in the fourteenth century reflecting the increasing political stability, growth of urban centres, establishment of serfdom and the development of the manorial system.